2017
DOI: 10.1016/j.jbmt.2017.03.008
|View full text |Cite
|
Sign up to set email alerts
|

The local twitch response during trigger point dry needling: Is it necessary for successful outcomes?

Abstract: and Discussion: Several studies show that eliciting a LTR does not correlate with changes in pain and disability, and multiple systematic reviews have failed to conclude whether the LTR is relevant to the outcome of TrPDN. Post needling soreness is consistently reported in studies using repeated in and out needling to elicit LTRs and increases in proportion to the number of needle insertions. In contrast, needle winding without LTRs to MTrPs and connective tissue is well supported in the literature, as it is l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(55 citation statements)
references
References 125 publications
3
52
0
Order By: Relevance
“…The occurrence of referred pain and local twitch response was significantly correlated to the pain intensity of active myofascial trigger point, the authors concluded that frequency of occurrence of referred pain is mainly depends on pain intensity of an active myofascial trigger point. Although the authors didn't correlate the presence of referred pain to the success of trigger point injection (11,12). None of patients had any complication during the procedure either none was reported after during follow up.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…The occurrence of referred pain and local twitch response was significantly correlated to the pain intensity of active myofascial trigger point, the authors concluded that frequency of occurrence of referred pain is mainly depends on pain intensity of an active myofascial trigger point. Although the authors didn't correlate the presence of referred pain to the success of trigger point injection (11,12). None of patients had any complication during the procedure either none was reported after during follow up.…”
Section: Resultsmentioning
confidence: 93%
“…Presence of local twitch response does not correlate with changes in pain and disability, and multiple systematic reviews have failed to conclude whether the local twitch response is relevant to the outcome of trigger point injection (11). Post needling soreness is consistently reported in studies using repeated in and out needling to elicit local twitch response and increases in proportion to the number of needle insertions, in contrast needle winding without local twitch response to myofascial trigger points and connective tissue is well supported in the literature,as it is linked to anti-nociception and factors related to tissue repair and remodeling (9,11), the positive biochemical changes in the trigger points after needling may simply be a wash out effect related to local vasodilation. While the local twitch response during trigger point injection may not unnecessary be associated with to better outcome for managing myofascial pain, further investigation is required.…”
Section: Resultsmentioning
confidence: 99%
“…15 There is one more important issue to consider: With dry needling, a local twitch response is considered to be a signal of a successful treatment, although recent research suggests that dry needling can be just as effective without the local twitch response. 16 In fact, the intensity of the stimulation needed to produce a local twitch response is intense, and it ''can increase the risk of tissue fibrosis in some cases.'' 17 Similarly, De Qi is considered to be essential for an effective acupuncture treatment outcome, but some research studies suggest that whether or not De Qi is achieved appears to have little or no effect on the treatment outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Elicitation of an LTR has classically been required for effective muscle activation [51]. Recent work disputes that an LTR is necessary, but acknowledges more research is required [67]. Decreased spontaneous electrical activity and acetylcholine levels are seen at active myofascial trigger points after dry needling in rats [68].…”
Section: Muscle Activationmentioning
confidence: 99%